Three Generations Under One Roof? : A Study of Interhousehold Transfers Among Sandwich Generation in Indonesia - Vianey Weda Rahesti; I Dewa Gede Karma Wisana (Jurnal Ekonomi dan Studi Pembangunan, 2025)
Empirical studies show some negative effects that arise in sandwich generation households. Even the negative impact of the sandwich generation raises the behavior that they want to leave the house. However, the empirical studies only measure sandwich generation if the parents live in the households, so it is necessary to recalculate sandwich generation households in Indonesia through an interhousehold transfer mechanism. This study examines interhousehold transfer differences among sandwich-generation households between parents, siblings, and others in Indonesia. Using Indonesian Family Life Survey (IFLS) 2014, this study found that 4.539 or 28,6 percent of households are classified as the sandwich generation, both if the elderly live in the household and the elderly doesn’t live in the household. Tobit regression analysis shows that non-one-roof sandwich generation households spend an interhousehold transfer 56,4 percent higher than one-roof sandwich generation households